2009
DOI: 10.1097/fbp.0b013e3283305ea2
|View full text |Cite
|
Sign up to set email alerts
|

Performance under a Go/No-go task in rats selected for high and low impulsivity with a delay-discounting procedure

Abstract: Research with animals and humans suggests that impulsivity is both a determinant and a consequence of drug abuse. In the present study, rats screened for high (HiI) or low (LoI) impulsivity using a delay-discounting task were compared on a Go/No-go procedure for intravenous cocaine (0.4 mg/kg) or saccharin pellets (0.1%). An additional aim was to examine the effects of previous cocaine exposure on impulsive choice. Thus, following Go/No-go testing, HiI and LoI rats were reevaluated on delay discounting. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…This is consistent with previous studies suggesting that higher delay reward discounting functions as a predisposing risk factor for alcohol and nicotine use (e.g., Anker, Zlebnik, Gliddon, & Carroll, 2009; Audrain-McGovern, et al, 2004; Perry, Nelson, Anderson, Morgan, & Carroll, 2007). It is plausible that those exhibiting higher delay reward discounting will not only be more likely to drink or smoke, but may also have a higher probability of concurrent use.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with previous studies suggesting that higher delay reward discounting functions as a predisposing risk factor for alcohol and nicotine use (e.g., Anker, Zlebnik, Gliddon, & Carroll, 2009; Audrain-McGovern, et al, 2004; Perry, Nelson, Anderson, Morgan, & Carroll, 2007). It is plausible that those exhibiting higher delay reward discounting will not only be more likely to drink or smoke, but may also have a higher probability of concurrent use.…”
Section: Discussionsupporting
confidence: 93%
“…cocaine, amphetamine and alcohol) in comparable delayed reward tasks in both animals and humans (e.g. Anker et al 2009;Cardinal et al 2000;Evenden and Ryan 1996;Helms et al 2006;Reynolds et al 2006b;Stanis et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that substances of abuse, and psychostimulants in particular, increase levels of impulsive choice and disinhibition in humans and laboratory animals (e.g. Anker et al 2009;Fillmore et al 2002;Harrison et al 1997;Helms et al 2006;Paine and Olmstead 2004;Stanis et al 2008;Van Gaalen et al 2006;but see De Wit et al 2002;Cardinal et al 2000;Fillmore et al 2006). Such findings suggest that psychostimulant abuse may itself lead to the heightened impulsivity often observed in chronic drug abusers (e.g.…”
Section: Introductionmentioning
confidence: 94%
“…The results of this study are also consistent with previous work in rodents showing that chronic experimenter-administered cocaine can cause elevated impulsive choice, and in combination with our previous findings using experimenter-administered cocaine (Simon et al, 2007), they suggest that the route of administration is less of a critical factor than the amount of cocaine intake (Dandy & Gatch, 2009; Setlow et al, 2009). A recent paper by Anker, Zlebnik et al (2009) reported that prior cocaine self-administration experience caused an increase in impulsive choice in a delay discounting task when rats were tested immediately following cocaine cessation (this effect was specific to a subset of rats that displayed low levels of impulsive choice prior to cocaine experience). The present results extend these findings by showing that self-administered cocaine-induced elevations in impulsive choice can persist several months after cocaine cessation.…”
Section: Discussionmentioning
confidence: 99%